MEKANISME GOOD CORPORATE GOVERNANCE, LEVERAGE DAN KINERJA KEUANGAN PERUSAHAAN - Oktavia, Evi (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2017)
The purpose of this research is to explain an empirical evidence about the effect of GoodCorporate Governance (GCG) mechanism and leverage on financial performance, and definewhich of the most important variables having powerful impact on the firm financial performance.Good Corporate Governance mechanism measured by using board gender, board of directors,board of commissioner, audit committee, and institutional ownership variables. Leveragemeasured by using Debt to Equity Ratio (DER) variable, while financial performance measuredby using Return on Equity (ROE) variable. This research is using secondary data, such as thefinancial report, idx statistic report, and other related information of financial industry listed inIndonesia Stock Exchange for the period of 2011 to 2015. The sample used in this research were23 companies which selected by using purposive sampling method. In this study, panel dataregression methods have been conducted to explain the effect of GCG and leverage on the firmfinancial performance.The results show that board gender has a positive and significant effect on the firmfinancial performance. Meanwhile, boards of directors, board of commissioner, audit committeeand leverage haveno significant effect on the firm financial performance. Moreover, institutionalownership has a positive effect and no significant on the firm financial performance.